FINANCIAL PERFORMANCE ANALYSIS OF CONVENTIONAL AND SHARIA BANKS (Studies in the Form of state-owned Bank ) - Dio Sasta Yuhansyah; Unti Ludigdo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to analyze how the performance of State-Owned Sharia Bank compared to State-Owned Conventional Bank. It also aims to analyze the alternative of State-Owned Sharia Bank establishment. Indicators of bank performance assessment are based on bank health assessment which assessed through capital, asset quality, management, earning, liquidity. The population in this study is State-Owned Bank which will be the main candidate for establishment of State-Owned Sharia Bank, both the conventional and sharia entities with total 6 (six) banks, namely : PT. Bank Rakyat Indonesia, Persero (Tbk), PT. Bank Mandiri, Persero (Tbk), PT. Bank Nasional Indonesia, Persero (Tbk), PT. Bank BRI Syariah, Persero, PT. Bank Syariah Mandiri, Persero, PT. Bank BNI Syariah, Persero. This research was conducted using analysis of comparative data that is comparing one data with the other's data. CAMEL variables which used to analyze the health rate of the bank of 8 (eight) ratios, that are : capital adequacy ratio (CAR), non performing loan (NPL), net profit margin (NPM), return on asset (ROA), return on equity (ROE), net interest margin (NIM), operating expense to operating income (BOPO), and loan to deposit ratio (LDR). The type of data used is quantitive data in the form of annual reports of banks during the period of 2010-2012. The results of this study indicate that conventional banks have better performance than Sharia Banks. In addition, alternative establishment of state-owned Sharia Banks wich reflect better performance is by merging Sharia and Conventional entities that exist under the same bank. Keywords: performance, State-Owned Sharia Bank, CAMEL (capital, asset, management, earning, liquidity), CAR, NPL, NPM, ROA, ROE, NIM, BOPO, LDR, comparative